Usage of Information and Communication Technology to Support Innovative Library Services in Universities: A Case of the University of Dar es Salaam Wilbert Chagula Library - Fidelis, Antidius (University of Dar es Salaam Library Journal, 2019)
This study investigated the application of Information and Communication Technologies (ICTs) in supporting innovative services at the University of Dar es Salaam (UDSM) Wilbert Chagula Library. It focused on ICT facilities available in the UDSM Library, ascertained usage of ICT facilities in offering innovative Library services, and factors influencing usage of ICT'S in the Library to provide innovative library services. The study employed a mixed methods in whi1ch a questionnaire, interview and observation guides were used to collect data from a sample of 50 respondents that included seven Heads of Sections, ten academic, thirty administrative and, two ICT staff, and the Director of Library Services. In general, the study ' s findings revealed that a majority of respondents are moderately skilled in the usage of ICTs which they obtained through on the job training, in-house classroom training organized by the UDSM Library, attend local and international seminars/workshops, international seminars/workshops and through professional training. The findings further revealed that, ICTs is used to offer innovative library services at UDSM Library. These services include: virtual desk services, provision of electronic resources and databases chat with a librarian, literature searches, QR code access, ask a librarian, and establishing institutional repositories.